Diagnostic value of plasma P‐tau217 in frontotemporal dementia spectrum disorders. (December 2021) - Rojas, Julio C.; Vandevrede, Lawren; Heuer, Hilary W.; Toller, Gianina; Thijssen, Elisabeth H.; Proctor, Nicholas; Forsberg, Leah K.; Brushaber, Danielle; Ramos, Eliana Marisa; Coppola, Giovanni; Appleby, Brian; Bordelon, Yvette M.; et al.
Abstract: Background: Frontotemporal dementia spectrum disorders (FTD) display complex neuropathological substrates and poor clinicopathological correlations, which hinders therapy development. Plasma P‐tau217 is an emerging tool to screen for Alzheimer's disease (AD) pathology and may have diagnostic value in FTD. Method: Plasma P‐tau217 was measured cross‐sectionally by electrochemiluminescence in FTD patients referred to ALLFTD from ARTFL (n = 628, 45.7% female, median age 66 ± 12 years). P‐tau217 differences by baseline phenotype, disease severity and genotype were determined with non‐parametric tests and general linear models. Associations between P‐tau217 and measures of disease severity and neuropsychological performance were determined with linear regressions corrected for age, sex, phenotype and APOE . Result: The sample included 33% behavioral variant FTD, 23.6% primary progressive aphasia (PPA), 28.5% atypical parkinsonism, 1.6% amnestic dementia (AmDem), 2.8% FTD/motoneuron disease, 3% mild cognitive/behavioral impairment and 7.5% healthy controls. Only 1.6% carried FTD‐causing mutations. P‐tau217 was not related to age (r = 0.034, 95%CI ‐0.03 – 0.12, p = 0.4). Compared to controls (0.18 ± 0.07 pg/mL), P‐tau217 was elevated only in AmDem (0.58 ± 0.9 pg/mL, p = 0.001) and logopenic PPA (lvPPA, 0.71 ± 0.62 pg/mL p < 0.001). P‐tau217 ≥ 0.42 pg/mL effectively discriminated AmDem and lvPPA from all other phenotypes (AUC 0.87, 95%CI 0.77 – 0.96, p = 0.001, 77% sensitivity, 92% specificity). AmDem (60%) and lvPPA (91.7%) had the highest prevalence of high (≥ 0.42 pg/mL) P‐tau217, and the highest prevalence of APOE4 (AmDem 40%, lvPPA 63.6%). APOE4 carriers (0.23 ± 0.22 pg/mL) had higher P‐tau217, than non‐carriers (0.19 ± 0.09 pg/mL), regardless of phenotype ( APOE effect p = .002, APOE x phenotype, p = 0.44). P‐tau217 was associated with worse clinical severity, mood, memory and executive function, but not with worse motor symptoms or social cognition. Conclusion: When FTD is suspected, high plasma P‐tau217 is strongly associated with amnestic dementia and logopenic PPA phenotypes. Pending completion of ongoing neuropathological, CSF and molecular neuroimaging analyses, the data support the use of plasma P‐tau217 to identify atypical AD as a cause or AD as a co‐pathology contributing to FTD clinical presentation.